Cost-effectiveness of nutrition and dietetic interventions in health - Orozco-González, Claudia (2019)
Introduction: Nutritional and dietary strategies aim to improve health. Studies of economic costs allow to evaluate interventions as well as to observe the costs and the benefits. Nutritional strategies have been developed whit low cost and high effectiveness to reduce the incidence of diseases, which is why they play an important role in the recovery and preservation of health. Material and methods: Systematic search in different databases. Including cost-effectiveness articles from the institutional point of view, of nutritional and dietary interventions from 1980 to 2018. The studies were grouped according to the type of intervention. In these, the objective and the differences of the simulation studies and the clinical-economic studies were compared. Results: 34 articles were included. All were randomized clinical trials, both in the studies taken from the literature to do the simulation studies and in the clinical-economic studies. Conclusions: Not all publications report the effectiveness units in the same monetary system, nor do they define effectiveness in the same way, however, nutritional and dietary intervention strategies are effective in reducing hospitalization days, improving vital forecasts and general health status of patients, so that its cost is not only depreciable, but should be considered as an essential part of health interventions.